AKTIVITAS ANTI FUNGI PIGMEN MERAH Penicillium purpurogenum TERHADAP Fusarium oxysporum - S. Widayati; Tatang Sopandi (FMIPA : Universitas PGRI Adi Buana, 2017)
Penicillium purpurogenum is known to be producing red pigment, pigment produced microbial activity, this research aims to demonstrate the activity of red pigment Penicillium purpurogenum antifungi against diameter and number of Fusarium oxysporum colonies, research done in the laboratory of Microbiology Adi Buana Surabaya University. This study used a randomized complete design (RAL) and Penicillium purpurogenum red pigment treatment concentrations of 0%, 0.5%, 1.0%, 1.5% and Ciprofloxacin 1.0%. Each treatment was repeated 4 (four) times, the research was carried out in vitro on medium PDA. The results showed that the red pigment resistance power P. purpurogenum 1.5% a significant effect (P < 0.05) against growth of fungi F. oxysporum and the number of colonies of fungis F. oxysporum compared red pigment resistance power P. purpurogenum 0% and 0.5%. growth of fungi F. oxysporum on PDA media containing pigment red P. purpurogenum 1.5% significant (P < 0.05) smaller than fungi growth F. oxysporum on PDA media containing pigment red P. purpurogenum 0% and 0.5%. Research results can be concluded that use of red pigment of P. purpurogenum can inhibit growth and the number of colonies of fungis F. oxysporum. Keyword: Red pigment, Penicilliumpur purogenum, Antifungi, Fusarium oxysporum.